IMPLEMENTASI ASESMEN NONKOGNITIF PADA ASPEK KESIAPAN BELAJAR BAGI SISWA KELAS IV - Odje, Maria Stefania; Ngadha, Christina; Lawe, Yosefina Uge; Ceme, Margareta (Jurnal Ilmiah Mandalika Education (MADU), 2024)
This research aims to explore the application of non-cognitive diagnostic assessments related to learning readiness and learning styles of grade IV students at SDK Tanalodu, Ngada Regency. The research method used is descriptive analytical with a qualitative approach. Data was collected through questionnaires, interviews and direct observation. The results of the analysis show that the majority of students (80.79%) show fairly good or higher learning readiness, with 46.16% in the fairly good category and 34.63% in the good category. Nevertheless, 19.21% of students showed the poor category, highlighting the need for additional attention to them. Variations in student learning styles were identified with the dominance of kinesthetic style (47.11%), followed by auditory style (26.95%) and visual style (26.95%). These findings emphasize the importance of considering learning style preferences in developing learning strategies that effectively support student learning success. This research provides a comprehensive picture of students' learning readiness and learning styles at SDK Tanalodu, with implications for the adoption of more adaptive and personalized learning approaches according to individual learning needs